Early regional wall distension is strongly associated with vulnerability to ventricular fibrillation but not arrhythmia triggers following coronary occlusion in vivo. (November 2017) - Barrabés, José A.; Inserte, Javier; Rodríguez-Sinovas, Antonio; Ruiz-Meana, Marisol; Garcia-Dorado, David
Abstract: Wall stress may favor ischemic ventricular arrhythmias, yet its association with ventricular fibrillation (VF) or ventricular ectopy has been inconsistent among studies and its potential arrhythmogenicity across the cardiac cycle is unclear. In 91 open-chest pigs undergoing 40–50 min left anterior descending artery occlusion, we assessed the association between diastolic or systolic distension of the ischemic area and the incidence of ventricular premature beats (VPBs) and VF. End-diastolic segment length (EDL) and systolic bulging ([maximum systolic length–EDL] × 100/EDL) were measured by ultrasonic crystals. Fifteen minutes after occlusion, EDL increased to 112.7 ± 5.6% of baseline (P < 0.001) and systolic bulging averaged 3.4 ± 2.2%. Median VPB number was 52 (IQR, 16–110), 2 (0–7) in phase Ia and 49 (13–94) in phase Ib. VF occurred in 26 animals (28.6%), the first episode appearing 24 ± 6 min after occlusion. EDL increase was associated with subsequent VF (115.9 ± 5.7 and 111.4 ± 5.1% in animals with and without VF, P < 0.001) and with the number of VF episodes (P = 0.001) but not with VPB number, overall (r = 0.028, P = 0.801) or in phases Ia or Ib. Systolic bulging was related neither to VF occurrence (3.2 ± 2.2 and 3.5 ± 2.2%, respectively, P = 0.561) nor to VBP number (r = 0.095, P = 0.397). EDL increase predicted VF after adjusting for ischemic area size and K + levels (odds ratio for 1% increase: 1.17, 95%CI 1.06–1.29, P = 0.001). Thus, diastolic regional ventricular distension predicts VF occurrence after coronary occlusion whereas neither diastolic nor systolic distension is associated with ventricular ectopy, which suggests that distension favors VF by acting on the arrhythmic substrate but not on arrhythmia triggers.